A panel of plasma microRNAs improves the assessment of surrogate markers of cardiovascular disease in rheumatoid arthritis patients. (1st September 2022) - Llop, Didac; Ibarretxe, Daiana; Plana, Núria; Rosales, Roser; Taverner, Delia; Masana, Lluís; Vallvé, Joan Carles; Paredes, Silvia
Abstract: Objective: Patients with RA present increased risk of cardiovascular (CV) disease compared with the general population. Moreover, CV risk factors that have a causal relationship with atherosclerosis do not seem to fully explain the accelerated process that they exhibit. We evaluated the association of a 10 microRNAs panel with surrogate markers of subclinical arteriosclerosis [carotid intima-media thickness (cIMT), carotid plaque presence (cPP), pulse wave velocity (PWV) and distensibility] in a cohort of RA patients. Material and methods: A total of 199 patients with RA were included. Surrogate markers of arteriosclerosis were measured with My Lab 60 X-Vision sonographer. MicroRNAs were extracted from plasma and quantified with qPCR. Multivariate models and classification methods were performed. Results: Multivariate models showed that microRNAs-24 (β = 15.48), 125a (β = 9.93), 132 (β = 11.52), 146 (β = 15.12), 191 (β = 13.25) and 223 (β = 13.30) were associated with cIMT globally. MicroRNA-24 [odds ratio (OR) = 0.41], 146 (OR = 0.36) and Let7a (OR = 0.23) were associated with cPP in men. Including the microRNAs in a partial least square discriminant analysis model properly classified men with and without cPP. MicroRNA-96 (β = –0.28) was associated with PWV in male patients. Finally, several miRNAs were also associated with cIMT, cPP and arterial stiffness in the high DAS28 group and in the earlier tertile groups of disease duration. Conclusion: Plasmatic expression of microRNA-24, 96, 103, 125a, 132, 146, 191, 223 and Let7a were associated with surrogate markers of CV disease and could be predictors of CV risk in patients with RA.